Peningkatan Keterampilan Proses Sains Siswa Melalui Model Pembelajaran Inkuiri Pada Materi Elastisitas Bahan - Venty Sopacua (Jurusan Pendidikan MIPA FKIP Universitas Pattimura, 2020)
This study aims to improve science process skills of high school students through inquiry model on material elasticity subject. The experimental design of learning applied by using one group pretest-posttest design tested on XI MIA5 and XI MIA4 classes with a total sample of 30 students. The data collected includes science process skill data, observation data, and student response data. Data analysis techniques used include; 1) qualitative descriptive analysis of skills of science processes, students’ activities and responses. 2) parametric statistical analysis of normality test, homogeneity test, and t-test. The result of the research indicates that: 1) there is a significant improvement of science process skill in every indicator of students' science process skill including determining variables, interpreting, summarizing, formulating problems, and formulating hypotheses. 2) experiment is the most prominent students’ 'activities, and 3) The students' response after taught using the inquiry model is very positive, with the highest percentage of student response is with teacher guidance when working on the students worksheet. Based on the results of this study, inquiry model can improve science process skills of students of SMAN 5 Ambon on the subject of elasticity material